Utilizing Technology to Enhance the Effectiveness of Social Studies Learning in Elementary Schools/MI - Wulandari, Algusti; Pratiwi Husain, Alma (Jurnal Ilmiah Teunuleh, 2025)
The utilization of technology in education has rapidly evolved, including in the teaching of Social Studies at the elementary school and Madrasah Ibtidaiyah (SD/MI) levels. Technology offers various innovations in teaching methods, ranging from interactive digital media and computer-based simulations to online assessments that enable a more effective and engaging learning process for students. This study aims to analyze how technology can enhance the effectiveness of Social Studies learning, identify the benefits gained, and examine the challenges in its implementation. The research employs a literature review method by analyzing various academic sources, including journals, books, and relevant scholarly articles. The findings indicate that the use of technology enhances students' understanding of Social Studies concepts, increases learning motivation through educational games and simulations, and facilitates teachers in conducting digital-based assessments. However, challenges such as limited infrastructure and teachers' readiness to adopt technology remain significant obstacles. Therefore, policies supporting the integration of technology in education are necessary, including teacher training and improved access to technological devices in schools. With the right strategies, technology can serve as an effective tool to enhance the quality of Social Studies learning in SD/MI, allowing students to experience a more interactive and meaningful learning process.